A COMPARATIVE STUDY OF HEADLINE WRITING IN BUSINESS NEWS - Thongsombat, Kittipong; Chatdecha, Chanika (วารสารนิสิตวัง, 2025)
The objective of this research were to 1) investigate the headline writing techniques in Business News in the Bangkok Post, The New York Times, and the Financial Times, 2) analyze the frequency of occurrence of various headline-writing techniques in business news across The Bangkok Post, The New York Times, and The Financial Times and 3) compare the frequency of occurrence of each headline-writing technique in business news among The Bangkok Post, The New York Times, and The Financial Times. The sample included headlines published from August to October 2023, with a total of 700 headlines including The Bangkok Post: 255 headlines, The New York Times: 273 headlines, and The Financial Times: 172 headlines. Statistics used in data analysis include frequency and percentage. The research results found that : (1) Out of 10 techniques in the study, the Bangkok Post deployed eight techniques while the Financial Times and the New York Times deployed only seven and six techniques respectively. Two techniques-colon for ‘say’ and nominalization-were not found at all in any of the newspapers. (2) The Bangkok Post got the most occurrences of loaded words (f=149, 38.21%), followed by the use of present simple tense (f=130, 33.33%). In the Financial Times, the most dominant technique observed was the use of loaded words with 147 occurrences (40.61%) with the present simple tense (f=131, 36.19%.) coming in second. The New York Times, which only six techniques were observed, had the most frequently used technique in loaded word with 156 occurrences (49.21%) and the use of simple tense is second with 111 occurrences (35.02%). (3) Their most frequently used technique and also the top 4 techniques were the same, namely; loaded words, present simple tense, omission of auxiliary verbs and idioms. The use of loaded words was found the most in all the three media. The New York Times has the most frequently used technique in loaded words with 156 occurrences (49.21%) while The Financial Times (f=147, 40.61%) and The Bangkok Post (f=149, 38.21%). The use of present simple tense was also ranked second in all three newspapers.